New giant penguin bones from Antarctica: Systematic and paleobiological significance - Acosta Hospitaleche, Carolina Ileana Alicia (Comptes Rendus Palevol)
A tarsometatarsus and a fragmented humerus of striking dimensions recently collected in the Late Eocene locality DPV 13/84 Submeseta Formation-level 38 Submeseta II-, Seymour (Marambio) Island, Antarctic Peninsula were both assigned to Palaeeudyptes klekowskii. According to estimates, the tarsometatarsus would belong to the largest and most massive penguin described so far. This bird was probably a piscivorous penguin, with high diving ability for catching prey. Although the humerus is not an appropriate element for body mass or body length assessments, it also belonged to a huge penguin. Un tarsometatarsus et un humérus fragmenté d’énormes dimensions, récemment recueillis dans l’Éocène supérieur DPV 13/84 (niveau 38, Submeseta II) de la formation Submeseta de l’île Seymour (Marambio), péninsule Antarctique, ont été attribués à Palaeeudyptes klekowskii. Selon les estimations, le tarsometatarsus appartiendrait au manchot le plus grand et le plus massif décrit jusqu’à présent. Cet oiseau a été un pingouin piscivore, avec une forte capacité de plongée sous-marine pour la capture des proies. Bien que l’humérus ne soit pas un élément approprié pour les évaluations de masse corporelle ou de longueur du corps, il appartenait aussi à un énorme manchot. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina